PENGARUH CAPITAL ADEQUACY RATIO, LOAN TO DEPOSIT RATIO, DANA PIHAK KETIGA, DAN DEBT TO EQUITY RATIO TERHADAP KINERJA KEUANGAN PERBANKAN DI INDONESIA (Studi Kasus Pada Bank Umum Yang Terdaftar Di BEI Tahun 2012-2015) - Dita Destiana Natali, 12.05.52.0118; Suwarti, Titiek (Students' Journal of Accounting and Banking, 2017)
This study aimed to analyze the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Third Party Funds (TPF), Debt to Equity Ratio (DER) on Return on Asset (ROA) in Commercial Banks. The population in this study is a Commercial Bank in Indonesia, which is listed on the Indonesia Stock Exchange (IDX) and is still in operation during the years 2012-2015. The sample in this study were obtained by purposive sampling method, samples are taken based on criteria used by researchers. Samples taken as many as 25 commercial banks. Data company then tested by means of multiple liniear regression analysis. The results showed that partially CAR and LDR no significant effect on ROA, DPK significant positive effect on ROA, and DER significant negative effect on ROA.Keywords: CAR, LDR, DPK, DER, ROA